Big data automatic analysis system and its applications in rockburst experiment. (8th April 2019) - Zhang, Yu; Bai, Yanping; He, Manchao; Lv, Zhaoyong; Li, Yongzhen
In 2006, State Key Laboratory for GeoMechanics and Deep Underground Engineering, GDLab for short, successfully reproduced the rockburst procedure indoors. Since then, a series of valuable research results has been gained in the area of rockburst mechanism. At the same time, there are some dilemmas, such as data storage dilemma, data analysis dilemma and prediction accuracy dilemma. GDLab has accumulated more than 500 TB data of rockburst experiment. But so far, the amount of analysed data is less than 5%. The primary cause of these dilemmas is the large amount of experimental data in the procedure of study of rockburst. In this paper, a novel big data automatic analysis system for rockburst experiment is proposed. Various modules and algorithms are designed and realised. Theoretical analysis and experimental research show that big data automatic analysis system for rockburst experiment can improve the existing research mechanism of rockburst. It also can make many impossible things become possible. The work of this paper lays a theoretical foundation for rockburst mechanism research.